Respeito aos direitos LGBTI+ no setor privado brasileiro : interfaces entre direitos humanos e empresas - Simões, Nathan Chagas (2024)
This dissertation refers to the final evaluative activity within the Academic Master's course in Human Rights, Citizenship, and Public Policies of the “PPGDH-UFPB”. The research "Respect for LGBTI+ rights in the Brazilian private sector: interfaces among human rights and companies" analyzes the policies and initiatives of companies’ part of the LGBTI+ Business and Rights Forum, and public supporters of the OHCHR Standards of Conduct, to investigate the existence of a growing rainbow market in Brazil. That is, companies that respect LGBTI+ rights and incorporate the agendas of sexual orientation, gender identity/expression, and sex characteristics (SOGIESC) into their operations and businesses. To this end, we will (i) explore the framework of [dis]respect for LGBTI+ rights in the Brazilian context, including human rights violations in the country, and discrimination processes in the private sector based on hatred and homotransphobia; (ii) debate the agenda of human rights and companies (BHR) and the corporate practices that address the themes of sexual orientation, gender identity/expression, sex characteristics and Diversity & Inclusion (D&I); (iii) present the results of multiple case studies of the companies part of the LGBTI+ Business and Rights Forum; and (iv) build a performance tool for the companies selected for the study with regard to the horizontal effectiveness of human rights and the efficiency and effectiveness of initiatives aimed at respecting LGBTI+ rights. With this dissertation, we seek to show that the Brazilian market must be held accountable in terms of LGBTI+ rights, not only as a potential entity of human rights abuse, but also as an active social transformation agent of protection, respect, and remedy of human rights.